Electrochemical behaviour of ionic liquid functionalized carbon supported Pt-Ru catalysts - Esteves, M. Alexandra (2013)
Ionic liquid (IL) functionalized carbon supported nanocatalysts, including platinum-ruthenium catalysts, have been under investigation to achieve better catalytic performance on polymer electrolyte membrane fuel cells. Ionic liquids have particular physical properties, which usually improve the stabillity and dispersion of metal nanosized particles, providing an increase of the electrochemical active surface area. In this work, the synthesis and the electrochemical behaviour of two new ionic liquid functionalizated carbon supported Pt-Ru nanocatalysts is investigated regarding the methanol oxidation reaction. Preliminary obtained results show that IL functionalization of carbon can produce supported catalysts with improved performances depending on the ionic liquid and on the reduction process used to produce the catalyst nanosized particles.